2020
DOI: 10.1101/2020.02.29.971382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Inherent Structural Difference Between Serine and Threonine Phosphorylation: Phosphothreonine Prefers an Ordered, Compact, Cyclic Conformation

Abstract: Phosphorylation and dephosphorylation of proteins by kinases and phosphatases are central to cellular responses and function. The structural effects of serine and threonine phosphorylation were examined in peptides and in proteins, by circular dichroism, NMR spectroscopy, bioinformatics analysis of the PDB, small-molecule X-ray crystallography, and computational investigations. Phosphorylation of both serine and threonine residues induces substantial conformational restriction in their physiologically more imp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 82 publications
2
17
0
Order By: Relevance
“…There is an inverse correlation between peptide helicity and 3 JPH, with the ahelical peptide 7 having the highest 3 JPH (9 Hz) and peptide 1 having the lowest (5.3 Hz). These values match very well with those found by Pandey et al 36 for pThrand pSer-containing peptides; the high value for peptide 7 suggests a well-defined P-O-C-H dihedral and ordered pThr side chain, whereas the lower values for peptides 3, 5 and 1 are consistent with a greater degree of pSer side chain freedom. The reduced value for 1 compared to 3, 5 and 6 is interesting and suggests altered dihedral propensities for the most helical pSer-containing peptide.…”
Section: Interaction Effects Shown Through Specific Side Chain Resonance Analysessupporting
confidence: 90%
See 2 more Smart Citations
“…There is an inverse correlation between peptide helicity and 3 JPH, with the ahelical peptide 7 having the highest 3 JPH (9 Hz) and peptide 1 having the lowest (5.3 Hz). These values match very well with those found by Pandey et al 36 for pThrand pSer-containing peptides; the high value for peptide 7 suggests a well-defined P-O-C-H dihedral and ordered pThr side chain, whereas the lower values for peptides 3, 5 and 1 are consistent with a greater degree of pSer side chain freedom. The reduced value for 1 compared to 3, 5 and 6 is interesting and suggests altered dihedral propensities for the most helical pSer-containing peptide.…”
Section: Interaction Effects Shown Through Specific Side Chain Resonance Analysessupporting
confidence: 90%
“…49 Moreover, recent studies have shown Thr phosphorylation promotes intra-residue hydrogen-bonding between the phosphate and the backbone amide, which would disrupt helix propagation in a manner analogous to the effect of Pro. 36 Taken together these results highlight the secondary structural sequence context of phosphorylation and highlight the potential for it to affect PPIs not only through orthosteric 13 or allosteric 50 changes in recognition features and switching off recognition by changing conformation, 14 but also through phospho-driven stabilization of an α-helical recognition motif.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, recent studies have shown Thr phosphorylation promotes intra-residue hydrogen-bonding between the phosphate and the backbone amide, which would disrupt helix propagation in a manner analogous to the effect of Pro. 27 Taken together these results highlight the secondary structural sequence context of phosphorylation and highlight the potential for it to affect PPIs not only through orthosteric 13 or allosteric 43 changes in recognition features and switching off recognition by changing conformation, 14 but also through phospho-driven stabilization of an α-helical recognition motif. piperidine: formic acid (75:20:5) solution (6 mL), room temperature method (5 min), wash with DMF (15 mL), add DMF: piperidine: formic acid (75:20:5) solution (6 mL), room temperature method (5 min), wash with DMF (15 mL), clean resin dip tube, wash with DMF (15 mL).…”
Section: Discussionmentioning
confidence: 73%
“…Such a conformation is incompatible with a helical conformation and is evidently not countered by the benefit of side-chain hydrogen-bonding as for pSer (peptide 1). 27 The effect of pH on helicity for peptide 1 provided useful insights on the contribution of charge-based interactions between side chains (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%